Xanthogranulomatous pyelonephritis with nephrocutanous fistula and coexisting renal replacement lipomatosis - The report of a rare case - Kiris, A; Kocakoc, E; Poyraz, AK; Dagli, F; Boztosun, Y (Elsevier Science Inc, 2005)
Renal replacement lipomatosis (RRL) is the result of rare, usually unilateral, and severe atrophy and destruction of the renal parenchyma often caused by renal calculi. It may be associated with, sometimes, aging, atrophy, long-standing chronic inflammation and urinary infection, such as renal tuberculosis. We report magnetic resonance (MR) and computed tomography (CT) findings of our case, which has xanthogranulomatous pyelonephritis (XGP) and RRL additionally associated with nephrocutanous fistula. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: xanthogranulomatous pyelonephritis; nephrocutanous fistula; renal replacement lipomatosis; MR; CT